Pengembangan Sistem Pakar Diagnosa Hipertensi Berbasis Web Menggunakan Klasifikasi Naive Bayes - Rauzana - Rauzana; Asrianda - Asrianda; Muhammad Fikry - Muhammad Fikry; Ramadhani - Ramadhani (Journal of Tourism Sciences, Technology and Industry, 2025)
Hypertension is a degenerative disease often referred to as a silent killer because it can trigger serious complications such as stroke, heart failure, and kidney damage. Limited access to medical personnel causes delays in diagnosis and treatment. This study designs a web-based expert system to diagnose hypertension using the Naive Bayes method. The system was developed using PHP programming language and MySQL database. Testing was conducted on 6 datasets, resulting in a diagnostic accuracy of 80%. This system is expected to help the community recognize hypertension symptoms and provide preventive and initial treatment solutions.